Aquaponics Development Strategy through the Empowerment of PKK Women's Groups in Palu City, Central Sulawesi - Angela Destalia Arumpone; Samliok Ndobe; Alimudin Laapo; Novalina Serdiati; Nasmia (Agricultural Science, 2026)
Limited urban land and women's low technical capacity in integrated agriculture necessitate an adaptive, technology-based empowerment strategy. This study examines the level of understanding of aquaponics cultivation among members of the Dasawisma Melati PKK group in Tanamodindi Urban Village, Palu City. It identifies development constraints, opportunities, and strategic formulations. The novelty of this research lies in integrating a mixed-methods approach with SWOT-AHP analysis to empower urban PKK women's groups. This area remains under-investigated empirically in Indonesia. The study involved 13 active group members over eight weeks (October–December 2025). It used Focus Group Discussions (FGDs), Likert-scale questionnaires, in-depth interviews, field observations, and pre-tests and post-tests. Despite the small sample size (This approach is representative as it encompasses all active members directly involved in managing the Green Farm House facility. The cultivated commodities consisted of 350 African catfish (Clarias gariepinus) with a 6% feeding rate and 48 heads of lettuce (Lactuca sativa L.). The cultivation results showed that catfish biomass increased from 37 grams to 667 grams over eight weeks, with an 83.71% survival rate. The lettuce plants grew from 2 cm to 17–23 cm, with an average harvest weight of 156.3 grams per plant. Water quality remained stable at temperatures of 30–31 °C and a pH of 7. Although an increase in ammonia from 2.3 mg/L to 8.2 mg/L was observed—which theoretically approaches the toxicity threshold—it did not correlate with the high survival rate (; moderate positive correlation), thereby indicating potential fish adaptation or the effectiveness of the biofiltration system. Participants' understanding increased significantly from 54.02% to 85.13%. All variables, including program quality, participation, and socio-environmental benefits, shifted to the "very high" category. The Public Satisfaction Survey recorded an index of 101.25 (89.91% satisfaction level). The SWOT analysis placed the group in Quadrant I (IFAS 3.9; EFAS 3.8). Through AHP with a Consistency Ratio of 1.9%, four priority strategies were established, with routine training at the Green Farm House designated as the primary program (62% weight). This study demonstrates that aquaponics, grounded in the empowerment of PKK women, is effective at sustainably strengthening urban food security and holds potential as a replicable model for other cities. However, further research with larger sample sizes and longer observation periods is required.